The comparative study of the influence of the parameters of the technological process of abrasive flow machining of the nozzle holes of the fuel injectors on the performance of the injection system - Popa, Dorinel (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
Improving the performance of automobiles is achieved by ensuring the optimal spraying characteristics of the mixture in the combustion chamber, which is achieved by changing the geometric parameters of the fuel flow of the fuel fluid through the nozzle. To obtain good energy performance of thermal engines in order to reduce pollution, it is used as processing operation (finishing and rounding) of the entrance to the fuel injector nozzle hole, erosion processing. Hydroerosion processing is carried out by removing the material to the erosive particles that are suspended in a working fluid, as a carrier. From the analysis of this process it follows that the reduction of cavitation, the rounding of the nozzle inlet can reduce the wear caused by the diesel flow when the injection system is in operation and implicitly the reduction of the impact of pollution on the environment.